Eurytrema coelomaticum: updated morphology of adult worms using advanced microscopy experiments. (2020) - Leite, K.G.; Lopes-Torres, E.J.; Souza, J.G.R.; Neves, R.H.; Gomes, D.C.; Machado-Silva, J.R.
Abstract: Eurytrema coelomaticum is a digenean flatworm of ruminants that is the causative agent of eurytrematosis, a disease of veterinary health concern. Although modern techniques of morphological analysis have provided new insights about the morphology and anatomy of parasitic helminths, most studies on E . coelomaticum adults are based on conventional light microscopy. In the present study, a combined approach using brightfield, fluorescence, confocal and scanning electron microscopies (SEMs), together with the cryofracture technique, have updated morphological data on E. coelomaticum recovered from cattle in Rio de Janeiro State, Brazil. Light microscopy confirmed the presence of several structures present in the current description, such as suckers, pharynx, oesophagus, intestinal bifurcation and the cirrus-sac. Fluorescence stereomicroscopy revealed for the first time the cubic crystal protein inclusions in the forebody, which were further detailed by confocal and SEMs. Confocal microscopy provided detailed information of the muscular architecture associated with the attachment structures (suckers), digestive system (pharynx and oesophagus), egg-forming complex (ovary, Mehlis' gland and Laurer's canal) and male reproductive system, which are similar to those found in other digenean flukes. SEM images of cryofractured parasites showed mucus and developing eggs within uterine loops. It was demonstrated that the combination of advanced tools generated complementary information, confirming the importance of experimental morphology in parasitology. Therefore, the knowledge of the adult structural organization of E. coelomaticum was improved and this work has contributed to propose new morphological criteria to evaluate the effects of antiparasitic drugs on flukes of medical and veterinary importance.